La OPQ celebra los 150 años de la Tabla Periódica en París y Oporto - Salas, Paloma (2019)
In 2019, the sesquicentennial of the publication of the periodic table proposed by Dmitri Mendeleev is commemorated. As part of this celebration, the students selected by the 2018 Peruvian Chemistry Olympiad (OPQ) participated in two international competitions representing Peru.